Sequencing technology as a major impetus in the advancement of studies into rheumatism: A bibliometric study - Huang, Runzhi; Tang, Jieling; Wang, Siqiao; Liu, Yifan; Zhang, Mengyi; Jin, Minghao; Qin, Hengwei; Qian, Weijin; Lu, Yuwei; Yang, Yiting; Lu, Bingnan; Yao, Yuntao; et al. (Frontiers in Immunology, 2023)
Background: Rheumatism covers a wide range of diseases with complex clinical manifestations and causes tremendous burden on humans. Due to the technology barrier, our understanding of rheumatism was seriously hindered. However, with the prevailing appliance and rapid advancement of sequencing technology in the past decades, we were able to study rheumatism in a more precise and profound manner. Sequencing technology made huge contributions to the field and now is an indispensable component and powerful tool to study rheumatism. Methods: Publications on sequencing and rheumatism from January 1st, 2000, to April 25th, 2022, were retrieved from the Web of Science database. Bibliometrix was applied for the publication year, countries, authors, sources, citations, keywords, and co-word analysis. Results: 1374 obtained articles came from 62 countries and 350 sources, with a general rise in article amount during the past 22 years. USA and China were taking lead in the publication number and actively cooperated with other countries. Most prolific authors and most influential documents were identified to establish the historiography of the field. Hotspots and frontiers were assessed by keywords and co-occurrence analysis. Immunological and pathological process in rheumatism, classification, risks and susceptibility, biomarkers for diagnosis were among the heated themes for research. Conclusions: Sequencing technology had wide application in rheumatism with great potential. More efforts are advised to pour into the study of genetic patterns related with rheumatic susceptibility, pathogenesis, classification and disease activity, and novel biomarkers.